UJI PRASYARAT ANALISIS - Abdul Nasar; Dimas Hadi Saputra, Mochammad Rifan Arkaan, Muhammad Bimo Ferlyando, Muhammad Teguh Andriansyah, Put (Jurnal Ekonomi dan Bisnis, 2024)
Often the problems faced by researchers involve making decisions based on data regarding a scientific system. The truth and falsity of a statistical hypothesis will never be known with certainty, unless the entire population is observed or used as a research sample (Total Sampling). Inferential statistics relates to population estimates and statistical hypothesis testing from existing data or conditions or phenomena. Thus, inferential statistics functions to predict control of conditions or events. The truth and falsity of a statistical hypothesis will never be known with certainty, unless the entire population is observed or used as a research sample (Total Sampling). The formulation of a statistical hypothesis is influenced by the chance of an erroneous conclusion. If a researcher wants to find strong support for an estimate, the researcher will try to place his estimate in the form of a rejection of the estimate. The method used in this research is a survey method using Google Form, then the data is transferred to Excel to be entered into IBM SPSS. Where we carry out calculations. Based on the research results obtained, the f table value is obtained because the N1 value is 12 and the N2 value is 37 so the number obtained is 2.02.